INTERACTIVE LEARNING STRATEGIES FOR CHINESE LANGUAGE AT SMP KRISTEN SHINING STAR SRAGEN - Rudiansyah, Rudiansyah; Lianisyah, Ulfah Yanuar; Sugiarti, Tati; Adi, Dian Prasetyo; Avenida, Quinta (Jurnal Visi Ilmu Pendidikan, 2025)
This research reviews 'Interactive Learning Strategies of Chinese language at SMP Kristen Shining Star Sragen. The aim is to identify and analyze the Chinese interactive learning strategies implemented by the teachers in this school. Chinese language learning at every level of education is becoming increasingly important, considering the development and needs of globalization. An interactive approach to Chinese language learning is expected to improve students' motivation, comprehension and language skills. This research uses descriptive qualitative method, with data utilization through observation, interview, documentation, and Focus Group Discussion (FGD), as well as using books, journals, and relevant literature sources. The results show that the interactive learning strategies applied include using drills and role-playing techniques. This strategy is believed to create a fun learning atmosphere while activating students' participation. In addition, the factors that influence the effectiveness of this strategy include teacher readiness, supporting facilities and infrastructure, and student involvement in the teaching-learning process.